The role of tualang honey in modulating nociceptive responses in the thalamus of rapid eye movement (REM) sleep deprivation rat model - Shafie, Anis Syahirah Mohd (2022)
Rapid eye movement (REM) sleep deprivation has been postulated to contribute to the alteration of nociceptive responses; however, the causes and effects are poorly understood. The aim of this study was to investigate the effects of REM sleep deprivation on nociceptive behaviour score, histological changes, the level of oxidative stress parameters, and the level of NMDA R2 receptors in the thalamus of REM sleepdeprived rat model. Furthermore, this study also determined the effects of Tualang honey on the parameters investigated. Forty-eight Sprague-Dawley male rats were equally divided into four groups (n=12); free moving control (FMC), REM sleep deprivation for 72 hours (REMsd), REM sleep deprivation for 72 hours pretreated with Tualang honey (REMsdH) and tank control (TC). Tualang honey (1.2 g/kg body weight/ day) was given by oral gavage for 30 days prior to the REM sleep deprivation procedure. Following the experimental period, formalin test and nociceptive behaviour were conducted. The rats were sacrificed, and the thalamus was removed for histological examination and quantification of oxidative stress parameters and NMDA receptors levels. REMsdH group showed a significant decrease in nociceptive behaviour score compared to REMsd group (p<0.05). The number of Nissl-stained neurons was significantly higher in REMsdH compared to REMsd (p<0.05). Dark neurons were observed in the VPL region of the REMsd group but not in the REMsdH group. REMsdH showed a significant increase (p<0.001) in GSH, GR, SOD, and CAT levels but a significant decrease (p<0.001) in MDA and NMDA R2 levels in the thalamus compared to REMsd. In conclusion, the administration of Tualang honey has protective effects against the adverse effects of REM sleep deprivation.